2010
DOI: 10.1002/hep.23631
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Changes After High-Dose Ursodeoxycholic Acid Treatment in Primary Sclerosing Cholangitis: Relation to Disease Progression

Abstract: High-dose (28-30 mg/kg/day) ursodeoxycholic acid (UDCA) treatment improves serum liver tests in patients with primary sclerosing cholangitis (PSC) but does not improve survival and is associated with increased rates of serious adverse events. The mechanism for the latter undesired effect remains unclear. High-dose UDCA could result in the production of hepatotoxic bile acids, such as lithocholic acid (LCA), because of limited small bowel absorption of UDCA and conversion of UDCA by bacteria in the colon. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 33 publications
0
77
0
2
Order By: Relevance
“…Several studies have been published on the effect of UDCA on clinical symptoms, liver function tests, and serum bile acid levels in PSC. 26,27 However, bile acid composition in the gut of PSC patients remains uninvestigated, as does the effect of UDCA on fecal and mucosal bile acid composition. Regarding the effect of bile acid on the microbiota, it has been recently reported that increased bile production (as a result of a high-fat diet) has a significant impact on the composition and activity of the intestinal microbiota.…”
Section: 25mentioning
confidence: 99%
“…Several studies have been published on the effect of UDCA on clinical symptoms, liver function tests, and serum bile acid levels in PSC. 26,27 However, bile acid composition in the gut of PSC patients remains uninvestigated, as does the effect of UDCA on fecal and mucosal bile acid composition. Regarding the effect of bile acid on the microbiota, it has been recently reported that increased bile production (as a result of a high-fat diet) has a significant impact on the composition and activity of the intestinal microbiota.…”
Section: 25mentioning
confidence: 99%
“…Sinakos et al investigated the serum bile acid composition in patients in the high-dose UDCA arm and compared that with serum bile acids in patients in the control group (49). They found a significant expansion of the total serum bile acid pool and increased UDCA and LCA enrichment in the UDCA-treated patients versus the placebo group when compared to pretreatment levels (49). In addition, they found that the increase in total serum bile acid pool correlated with worse outcomes in patients with PSC (49).…”
Section: Apical Sodium-dependent Bile Acid Transporter Inhibitors Andmentioning
confidence: 97%
“…They found a significant expansion of the total serum bile acid pool and increased UDCA and LCA enrichment in the UDCA-treated patients versus the placebo group when compared to pretreatment levels (49). In addition, they found that the increase in total serum bile acid pool correlated with worse outcomes in patients with PSC (49). Together, these observations suggest that changes in the bile acid pool could be deleterious in patients with PSC, and alteration of the bile acid pool may be of therapeutic benefit in PSC.…”
Section: Apical Sodium-dependent Bile Acid Transporter Inhibitors Andmentioning
confidence: 98%
“…The use of UDCA in patients without BSEP function may be contraindicated. Notably, when UDCA was used at a high dose, in a clinical trial for primary sclerosing cholangitis, patients displayed significantly higher mortality, leading to premature termination of the trial (21,31).…”
Section: (Oh) T (Oh)2 T (Oh)3 T (Oh)4 T (Oh)5 (Ohmentioning
confidence: 99%